PERBANDINGAN HASIL BELAJAR FISIKA PADA MATERI POKOK ENERGI DENGAN MENGGUNAKAN METODE DISKUSI DAN METODE INKUIRI PADA SISWA KELAS VIII SMP NEGERI 1 BATANG ANGKOLA - Siregar, Dwi Aninditya (Jurnal Physics Education (PhysEdu), 2024)
This study aims to see a comparison of the results of studying physics in the subject matter of energy by using the method of discussion and inquiry method in class VIII SMP Negeri 1 Batang Angkola. The method used in this study is the experimental method, and conduct experiments on two classes. The population in this study were all eighth grade students of SMP Negeri 1 Batang Angkola consisting of 6 classes totaling 192 students. Samples were numbered 32 class X1 and X2 are 32 people were determined by cluster random sampling. This research instrument manifold observation sheet given to the observer to evaluate and test in the form of multiple-choice questions to test amounted to 20 and 20 aspects are assessed for observation sheet. The data collected were analyzed in two ways, namely descriptive analysis (to see a general overview of both variables) and statistical analysis (to test the proposed hypothesis whether accepted or rejected). Student learning outcomes using the discussion reaches an average value of 70.8 which is included in the category of "good", while the learning outcomes of students using inquiry method reaches an average value of 64.06 which is included in the category of "enough". Based on the results of hypothesis testing is done, obtained ttes = 2.21 while ttable at the level of 95% with an error rate of 5% df = N - 2 = 64-2 = 62 is 2:00. Thus it can be seen that ttes greater than ttable (2:21 > 2:00). This shows that the proposed hypothesis is accepted or approved truth, meaning that there is a significant comparison between the use of the method of discussion and inquiry method to student learning outcomes in energy pokok material in class VIII SMP Negeri 1 Batang Angkola.